Geriatric Nutritional Risk Index as a prognostic marker for predicting survival outcomes in patients with UTUC after radical nephroureterectomy - Lei Zheng; Jianjun Ye; Qiyou Wu; Jinhong Chen; Qihao Wang; Kai Chen; Qiang Wei; Yige Bao (Scientific Reports)
Abstract The purpose of this study was to determine the prognostic value of the Geriatric Nutritional Risk Index (GNRI) in patients with upper tract urothelial carcinoma (UTUC) after radical nephrectomy (RNU). A retrospective study of UTUC patients was conducted at West China Hospital between May 2016 and June 2019. The optimal cut-off point for GNRI was determined using the X-Tile procedure. Univariate and multivariate analyses were performed to identify predictors, and two- and four-year cancer-specific survival (CSS) prediction nomograms were created based on the results of the multivariate analyses. Furthermore, time-dependent ROC curve, calibration curve and decision curve analyses were conducted. A total of 219 patients with UTUC following RNU were identified and subsequently divided into three groups based on the critical values of GNRI (91.2, 98.8). GNRI was identified as a significant risk factor for CSS, with patients exhibiting higher GNRI demonstrating elevated CSS (hazard ratio = 0.58; 95% confidence interval, 0.32–0.92; P = 0.037). Furthermore, the GNRI-based nomogram demonstrated high predictive capacity for CSS, with areas under the curve of 0.810 and 0.842 for 2- and 4-year CSS, respectively. Preoperative GNRI is an independent predictor for CSS in UTUC patients who underwent RNU and should be considered as a promising personalized tool for clinical decision-making.